Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1164/rccm.201601-0070oc
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Orchestrates Lateral Transfer of Aspergillus fumigatus during Macrophage Cell Death

Abstract: Rationale: Pulmonary aspergillosis is a lethal mold infection in the immunocompromised host. Understanding initial control of infection and how this is altered in the immunocompromised host are key goals for comprehension of the pathogenesis of pulmonary aspergillosis.Objectives: To characterize the outcome of human macrophage infection with Aspergillus fumigatus and how this is altered in transplant recipients on calcineurin inhibitor immunosuppressants. Methods:We defined the outcome of human macrophage infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…For C. albicans, it is well established that within the macrophage phagosome, the fungi encounter significant nutrient stress, which must be dealt with in order for the fungi to continue to grow and escape the macrophage (77,78). Interestingly, Shah et al showed that A. fumigatus conidia of the CEA10 strain have the ability to germinate within the late phagosomes of macrophages (79). This germination initiates necroptotic cell death of macrophages, resulting in the lateral transfer of hyphae to other macrophages in order to prevent hyphal escape and maintain control of fungal germination, which is associated with the transcriptional upregulation of Il1a (79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For C. albicans, it is well established that within the macrophage phagosome, the fungi encounter significant nutrient stress, which must be dealt with in order for the fungi to continue to grow and escape the macrophage (77,78). Interestingly, Shah et al showed that A. fumigatus conidia of the CEA10 strain have the ability to germinate within the late phagosomes of macrophages (79). This germination initiates necroptotic cell death of macrophages, resulting in the lateral transfer of hyphae to other macrophages in order to prevent hyphal escape and maintain control of fungal germination, which is associated with the transcriptional upregulation of Il1a (79).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Shah et al showed that A. fumigatus conidia of the CEA10 strain have the ability to germinate within the late phagosomes of macrophages (79). This germination initiates necroptotic cell death of macrophages, resulting in the lateral transfer of hyphae to other macrophages in order to prevent hyphal escape and maintain control of fungal germination, which is associated with the transcriptional upregulation of Il1a (79). The metabolic response that enables this growth in A.…”
Section: Discussionmentioning
confidence: 99%
“…Post phagocytosis, melanin inhibits acidification of the phagolysosome by interfering with the translocation of the NADPH oxidase subunit p22 phox , contributing to conidial survival within the phagolysosome (Akoumianaki et al, 2016). Shedding light on macrophage-based mechanisms post-germination in the phagosome, it was shown that A. fumigatus germlings can be passed to a new macrophage to continue inhibition of growth and disease progression (Shah et al, 2016) furthering our understanding of dynamic macrophage interactions with A. fumigatus .…”
Section: Reviewmentioning
confidence: 99%
“…Alveolar macrophages have long been recognized as effector cells against A. fumigatus . A recent study has shown that this cell type controls the majority of fungal germination [20] . However, some organisms es-cape the late phagosome and are laterally transferred to other macrophages.…”
Section: Macrophages Inflammatory Monocytes Eosinophils and Naturamentioning
confidence: 99%
“…Intriguingly, the calcineurin inhibitor FK506 reduces macrophage death and lateral transfer, which results in uncontrolled fungal germination in macrophages. An additional innate cell type recently studied in A. fumigatus control is the CCR2+ inflammatory monocyte [20]. These cells are thought to function in transporting fungal antigens from the lung to the draining lymph node, where they prime CD4 T cell responses.…”
Section: Macrophages Inflammatory Monocytes Eosinophils and Naturamentioning
confidence: 99%